2016
DOI: 10.1080/14737175.2017.1260004
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet and childhood neurological disorders other than epilepsy: an overview

Abstract: In the last years, ketogenic diet (KD) has been experimentally utilized in various childhood neurologic disorders such as mitochondriopathies, alternating hemiplegia of childhood (AHC), brain tumors, migraine, and autism spectrum disorder (ASD). The aim of this review is to analyze how KD can target these different medical conditions, highlighting possible mechanisms involved. Areas covered: We have conducted an analysis on literature concerning KD use in mitochondriopathies, AHC, brain tumors, migraine, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 97 publications
0
23
0
Order By: Relevance
“…Ketogenic diets (KDs) for the dietary management of epilepsy and neurometabolic conditions have undergone a worldwide renaissance and a reported increase in use over recent decades . Clinical and scientific research has confirmed degrees of efficacy , revealed possible mechanistic insights and, more recently, indicated their potential as adjunctive treatments for an ever‐widening range of other medical conditions . However, acceptability of KDs and adherence to the requisite, habitual, very low‐carbohydrate, very high‐fat intake is known to be variable and problematic, particularly for adults .…”
Section: Introductionmentioning
confidence: 99%
“…Ketogenic diets (KDs) for the dietary management of epilepsy and neurometabolic conditions have undergone a worldwide renaissance and a reported increase in use over recent decades . Clinical and scientific research has confirmed degrees of efficacy , revealed possible mechanistic insights and, more recently, indicated their potential as adjunctive treatments for an ever‐widening range of other medical conditions . However, acceptability of KDs and adherence to the requisite, habitual, very low‐carbohydrate, very high‐fat intake is known to be variable and problematic, particularly for adults .…”
Section: Introductionmentioning
confidence: 99%
“…Findings may also add to the growing evidence for involvement of magnesium in migraine pathophysiology (1). Other studies show that Ca2+ and other ion channels are important in the mechanism of cortical spreading depression, which is believed to initiate migraine attacks (2). Thus, impaired function of cerebral Ca2+ channels may facilitate the initiation of attacks (10).…”
Section: Discussionmentioning
confidence: 74%
“…The calcium channels are known to regulate the release of serotonin. with impaired functioning of the channels, serotonin may not effectively be released or may be released in low quantities (2). As a consequence of this dip, a range of migraine symptoms begin to occur (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional benefit is that it may be easier for many individuals to comply with It also may be easier for many individuals to comply with, [195] increasing the likelihood of sustained adherence. Finally, the ketogenic diet (KD) has been examined, originally as a potential non-pharmacological strategy to reduce the frequency and severity of seizure activity in epileptic patients [196]. Through hermetic mechanisms, KD has been postulated to improve central metabolic function, [169,197,198] a critical factor in age-dependent neurocognitive decline [197].…”
Section: Other Dietary Patternsmentioning
confidence: 99%